Physicochemical and Bacteriological Analyses of Groundwater in the Periphery of the Bagmati River in Kathmandu Valley - Silwal, Sandhya; Shrestha, Sanjiv; Shrestha, Soniya; Khatiwada, Manisha; Jaishi, Anita (Kathmandu University Journal of Science Engineering and Technology, 2020)
The objective of this study was to assess the physicochemical and bacteriological quality of groundwater samples. A total of 34 samples were taken during the time period of June 6 to June 21 of 2016 from the groundwater sources in Kathmandu, located in the periphery of Bagmati river, from Chobhar to Sinamangal with approximate distance of 10 km. Site for study, sample collection, transportation, preservation and processing (bacteriological and physicochemical analyses) of samples were carried out following standard protocols issued by [1, 2]. Membrane filtration technique was employed for enumeration of indicator organism (coliform and thermotolerant coliform) and biochemical tests for its identification.